2003
DOI: 10.1590/s0100-84042003000400008
|View full text |Cite
|
Sign up to set email alerts
|

Ovule ontogenesis and megasporogenesis in Adesmia latifolia (Spreng.) Vog. (Leguminosae-Papilionoideae)

Abstract: -(Ovule ontogenesis and megasporogenesis in Adesmia latifolia (Spreng.) Vog. (Leguminosae-Papilionoideae)). The ovule ontogenesis and the megasporogenesis events were studied under bright field, fluorescence and scanning electron microscopy. The primordium is 3-zonate and gives rise to a hemianatropous, bitegmic and crassinucellate ovule. The archesporium may consist of one or more archesporial cells, but only one undergoes meiosis, forming a linear tetrad. Normally, only a single megaspore is functional in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
(32 reference statements)
2
14
0
2
Order By: Relevance
“…The nucellus of ovules in Fabaceae is crassinucellate (Prakash 1987;Faigón Soverna et al 2003;Moco & Mariath 2003;Galati et al 2006), which were also found in our species. This type has been considered to be the plesiomorphic condition in angiosperms (Sporne 1969).…”
Section: Discussionsupporting
confidence: 80%
“…The nucellus of ovules in Fabaceae is crassinucellate (Prakash 1987;Faigón Soverna et al 2003;Moco & Mariath 2003;Galati et al 2006), which were also found in our species. This type has been considered to be the plesiomorphic condition in angiosperms (Sporne 1969).…”
Section: Discussionsupporting
confidence: 80%
“…The absence of a micropylar nucellar beak is clearly shown in Figs 3, 6 and 11. Furthermore, in A. latifolia , the micropylar nucellus is almost completely reabsorbed at the mature embryo sac stage, and no nucellar beak is present (Moço, 2002; Moço & Mariath, 2004), as observed in the present work in both Adesmia species. Diverse micropylar haustoria are found in angiosperms.…”
Section: Resultssupporting
confidence: 85%
“…Vog. (Moço & Mariath, 2001, 2003, 2004; Moço, 2002) have been investigated. However, seed development has only been analysed in detail in Adesmia securigerifolia Herter (Izaguirre, Mérola & Beyhaut, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Embryological features can provide >50 characters associated with the development of anthers, ovules and seeds, contributing to a better understanding of the relationships among families and genera (Tobe, ). Studies such as the observations of ovule development have proved to be efficient in differentiating taxonomic groups, not only by confirming phylogenetic relationships but also by revealing evolutionary patterns within the groups (Tobe & Raven, ; Anton & Cocucci, ; Juncosa & Tobe, ; Tobe, ; Moço & Mariath, ; De Toni & Mariath, , ; Fagundes & Mariath, ).…”
Section: Introductionmentioning
confidence: 99%